(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The main principle of screening for cervical cancer is the early diagnosis of neoplastic processes. One one of the most important methods of the screening program is a biopsy of the cervix with a histological examination of the tissue. The aim of the work is a morphological study of cervical biopsies taken from 317 women aged 20 to 82 years, the study of the structure of background and precancerous diseases over 3 years (2013-2015). The most common background disease in women of the active reproductive period (from 20 to 40 years) was cervical ectopia (51%). In women of mature and older age (from 30 to 60 years) in the cervix, there is a predominance of dysregenerative and hyperplastic processes such as leukoplakia (84.7%) and polyps (80%). Among precancerous diseases, the maximum frequency of occurrence (71.7%) falls on cervical intraepithelial neoplasia of the 1st degree. Squamous cell carcinoma of the cervix was diagnosed in 1.6% of the cases studied, which is closely associated in frequency of occurrence with cervical intraepithelial neoplasia of the 3rd degree (1.9%).